Differential expression of Ia antigens by rheumatoid synovial lining cells. - Burmester, G R (1987)
The differential expression of Ia antigens was studied in freshly isolated rheumatoid nonlymphoid synovial lining cells (SLC) and rheumatoid synovial fibroblast cell lines cultured in the presence of Interferon-gamma, using a large panel of anti-Ia reagents with monomorphic or polymorphic specificities. All the HLA-DR or -DQ specificities detectable on the corresponding peripheral blood B cells were also expressed in freshly isolated SLC. However, in all instances, the number of DR-positive SLC exceeded the percentage of cells expressing DQ antigens. In addition, the epitope expression of Ia antigens varied within the DR or DQ populations of Ia molecules as revealed by polymorphic reagents. Double-label experiments or using the ingestion of Latex particles as a marker demonstrated that the synovial macrophages (type I SLC) primarily bear the DR+DQ+ phenotype, while there is an additional population of nonphagocytic SLC (previously termed type II SLC) that has a DR+ and monocyte marker negative phenotype but did not have detectable levels of DQ antigens as analyzed by both fluorescence microscopy and cell sorter analysis. This latter population frequently had a morphology showing dendritic processes and rapidly lost the expression of Ia antigens upon culture. Cells with a similar, primarily DR+ phenotype were readily obtained in synovial fibroblast cultures after treatment with Interferon-gamma. These data suggest that there are two populations of Ia+ synovial lining cells: the synovial macrophages (type I cells) with the DR+DQ+ phenotype, and cells probably related to fibroblasts with a DR+ phenotype without detectable DQ antigens (type II cells). The fact that the latter phenotype could be induced by Interferon-gamma treatment of cultured synovial fibroblasts suggests that this mediator may have a similar role in vivo in the activation of certain synovial cell populations.